The OH-initiated oxidation of atmospheric peroxyacetic acid: Experimental and model studies - H.H. Wu; Y. Wang; H. Li; L.B. Huang; D. Huang; H.Q. Shen; Y.N. Xing; Chen, Z. M. (Atmospheric Environment, 2017)
Peroxyacetic acid (PAA, CH3C(O)OOH) plays an important role in atmospheric chemistry, serving as reactive oxidant and affecting radical recycling. However, previous studies revealed an obvious gap between modelled and observed concentrations of atmospheric PAA, which may be partly ascribed to the uncertainty in the kinetics and mechanism of OH-oxidation. In this study, we measured the rate constant of OH radical reaction with PAA (kPAA+OH) and investigated the products in order to develop a more robust atmospheric PAA chemistry. Using the relative rates technique and employing toluene and metaxylene as reference compounds, the kPAA+OH was determined to be (9.4-11.9)*10-12 cm3 molecule-1 s-1 at 298 K and 1 atm, which is about (2.5-3.2) times larger than that parameter used in Master Chemical Mechanism v3.3.1 (MCM v3.3.1) (3.70*10-12 cm3 molecule-1 s-1). Incorporation of a box model and MCM v3.3.1 with revised PAA chemistry represented a better simulation of atmospheric PAA observed during Wangdu Campaign 2014, a rural site in North China Plain. It is found that OH-oxidation is an important sink of atmospheric PAA in this rural area, accounting for ~30% of the total loss. Moreover, the major terminal products of PAA-OH reaction were identified as formaldehyde (HCHO) and formic acid (HC(O)OH). The modelled results show that both primary and secondary chemistry play an important role in the large HCHO and HC(O)OH formation under experimental conditions. There should exist the channel of methyl H-abstraction for PAA-OH reaction, which may also provide routes to HCHO and HC(O)OH formation.